An intelligent robust cascaded control scheme for renewable energy based microgrid. Issue 10 (8th March 2022) - T, Vigneysh; Velamuri, Suresh; Kantipudi, MVV Prasad; Viriyasitavat, Wattana
Abstract: Handling the uncertainties in the utility grid and uncertainties in renewable energy sources is a main challenge to accomplish the modern grid code requirements. This article proposes a new control strategy based on interval type‐2 fuzzy sets for controlling the grid‐connected dispersed generation (DG) system tied to the distorted electric grid. The proposed control technique can easily model and handle the uncertainties in the system parameters and renewable energy sources. The existence of three‐dimensional membership functions of type‐2 fuzzy sets offers an additional degree of freedom to counter the uncertainties in the system. The proposed strategy is effective in improving the dynamic response during system uncertainties such as distortions in grid voltage, variations in grid frequency, variations in renewable energy sources and due to presence of non‐linear and unbalanced loads. Also, it improves the quality of the current being injected to the grid during uncertainties. The proposed control strategy is applied to control the dc side capacitor voltage as well as to control the current loop of the grid connected inverter. The proposed system is simulated in MATLAB Simulink environment and the performance is compared with traditional controllers to show the effectiveness of the proposed control strategy during system abnormalities.